2011
DOI: 10.1007/s11892-011-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Diabetic Kidney Disease

Abstract: The number of people with diabetic kidney disease continues to increase worldwide despite current treatments. Of the pathophysiologic mechanisms that have been identified in the development and progression of diabetic nephropathy, oxidative stress (more accurately described as increased levels of reactive oxygen species; ROS) is of major importance. The increase in ROS is due to both increased production and to decreased and/or inadequate antioxidant function. To date, human clinical trials with antioxidants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 57 publications
4
97
0
2
Order By: Relevance
“…In animal models, antioxidants have been shown to be effective in treating DN (21,22). In combination with the current human data showing an independent association between bilirubin and renal outcome, we speculate that treatments intended to slightly raise bilirubin levels might have a beneficial effect on progression of nephropathy in patients with type 2 diabetes and low bilirubin levels.…”
Section: Discussionsupporting
confidence: 58%
“…In animal models, antioxidants have been shown to be effective in treating DN (21,22). In combination with the current human data showing an independent association between bilirubin and renal outcome, we speculate that treatments intended to slightly raise bilirubin levels might have a beneficial effect on progression of nephropathy in patients with type 2 diabetes and low bilirubin levels.…”
Section: Discussionsupporting
confidence: 58%
“…32 There is a strong biologic rationale for inflammation, oxidative stress, and fibrosis, to be critical risk factors for renal disease progression in DKD. [33][34][35] Experimental research has shown that PTF diminishes renal tissue damage through beneficial anti-inflammatory, antioxidant, and antifibrotic effects, 17,36,37 resulting in attenuation of kidney disease progression. This outcome is maximized after combination with RAS blockers.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our recent studies demonstrated that NADPH oxidase-derived ROS production-mediated c-Src kinase activation was an upstream mediator of EGFR activation in renal proximal tubular epithelial cells in response to chronic angiotensin II treatment. 15 A recent study also indicated that inhibition of c-Src kinase prevented progression of diabetic nephropathy.…”
Section: Ros-mediated Podocyte C-src and Egfr/erk Phosphorylationmentioning
confidence: 96%
“…In the United States, diabetic kidney disease is now the major cause of end stage kidney disease 1 and increases the rate of other complications, such as cardiovascular disease. 2 Twenty to forty percent of all patients with diabetes will develop some form of kidney disease during their life.…”
mentioning
confidence: 99%